Workshop Penyusunan Bahan Ajar Kurikulum Merdeka dalam Meningkatkan Profesionalisme Guru di Sekolah Perbatasan Indonesia-Malaysia - Ramadhan, Iwan; Imran, Imran; Syahrudin, Husni; Ulfah, Maria; Ismiyani, Nining; Atmaja, Thomy Sastra; Dewantara, Jagad Aditya; Wisely, Vincent Obedly; Rokiaske, Rokiaske; Emita, Emita (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This service activity aims to increase the professionalism of teachers at schools on the Indonesia-Malaysia border in preparing independent curriculum teaching materials. The method of implementing this service uses participatory-based training. The partners involved are teachers at SMAN 1 Jagoi Babang on the Indonesia-Malaysia border. This service evaluation instrument includes participant satisfaction surveys, knowledge tests before and after the workshop, as well as direct observation of participant participation and skills. Data analysis was analyzed using descriptive statistical methods to describe the success rate of the workshop, as well as comparative analysis to see changes before and after the workshop. The results of this service show an increase in teachers' understanding of the preparation of teaching materials in the independent curriculum, as well as an increase in enthusiasm and skills in creating teaching modules. In addition, participants showed high interest in implementing differentiated learning and adapting to curriculum changes. It shows that there is a positive impact of service activities on teacher professionalism and readiness to face the demands of the new curriculum.